Does increased board independence reduce earnings management? Evidence from recent regulatory reforms - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2015)
In this paper, we examine whether recent regulatory reforms requiring majority board independence are effective in reducing earnings management. Firms that did not have a majority of independent directors prior to the reforms (referred to as non-compliance firms) are required to increase their board independence. We find that overall, compared to the other firms, noncompliance firms do not experience a significant decrease in the extent of earnings management from prior to the reforms to afterwards. However, we find that non-compliance firms with low information acquisition cost experience a significant reduction in earnings management compared with the other firms. The results hold for various proxies for information acquisition cost and earnings management. These findings indicate that independent directors’ monitoring is more effective in a richer information environment.